Prospective approaches for risk analysis in modern radiotherapy: the Italian experience and the contribution of medical physicists. Issue 1 (14th February 2014) - Begnozzi, L.; Cantone, M.C.; Longobardi, B.; Veronese, I.
<x content-type="archive" xml:space="preserve">Abstract</x> In the last few years there has been significant development of radiation therapy (RT) equipment with advanced imaging and delivery techniques, as well as treatment planning systems. From this perspective, proactive approaches for risk assessment were identified as a powerful tool in modern radiation oncology. A multidisciplinary working group (WG) has been established in the framework of the Italian association for medical physics (AIFM) to promote the use of prospective approaches in the radiotherapy scientific community. This paper describes the main actions carried out by the WG in order to collect information about the engagement of Italian medical physicists in the risk management process, in reporting possible incidents in RT and in the procedures of collecting and analysing near misses. In particular, the main scope of the study was to evaluate the actual level of experience in use of proactive risk analysis tools in modern RT by medical physicists. Finally, the measures implemented by the WG in order to promote the use of such approaches, and consequently to contribute to enhancing safety and radiation protection culture in radiation oncology are described.